A Review on the Effectiveness of Raised Crosswalks - Parsuraman, Jeyasaraniya; David Daniel, Basil (Recent Trends in Civil Engineering and Built Environment, 2023)
Speed was considered second-highest contributing to road crashes, particularly in free flow situations in the case of road accidents. Speeding on university campuses in Malaysia is also a problem. Out of control accidents have resulted in injuries and damages are more likely to occur in campus which can be linked to a speeding problem. This study is crucial in determining the importance of installation of raised crosswalks in reducing vehicle speed and improves pedestrian safety. A systematic review is conducted, and quantitative analysis was carried out to determine the effects of raised crosswalks on speed reduction and pedestrian safety. Almost all the studies shown positive results on speed reduction and pedestrian safety. A design of raised crosswalk is also proposed for installation in several locations in Universiti Tun Hussein Onn Malaysia.